IS RESTORATIVE JUSTICE AN APPROPRIATE LEGAL REMEDIATION FOR SEXUAL VIOLENCE? - Kazic, Ena; Ćorović, Rialda (Review of European and Comparative Law, 2019)
This paper questions applicability of restorative justice in cases of sexual violence. Specific nature and serious consequences of sexual violence are the reason why this question appeared. In order to find out the answer, authors represented the characteristics, mechanisms and nature of restorative justice, offering in the same time comparition of arguments in favor and against of applicability of restorative justice in this, particulary sensitive type of criminal offences. Together with review of different theoretical approaches to this matter, authors tested applicability of restorative justice in cases of sexual violence in Bosnia and Herzegovina. In this paper normative, comparative and historical scientific methods have been used.